P58 Barriers and facilitators to implementation of diet and physical activity interventions in schools-a dedipac (determinants of diet and physical activity) qualitative study. (2nd September 2017) - Hayes, CB; O'Shea, MP; Horodyska, K; Luszczynska, A; Langøien, LJ; Roos, G; Muellman, S; Pischke, CR; Bourdeaudhui, I De; Brug, J
Abstract : Background: This case study was undertaken in Ireland as part of the European DE terminants of D Iet and P hysical Ac tivity (DEDIPAC) Knowledge Hub. Two national interventions were chosen based on predetermined selection criteria: a Healthy Eating Programme (HEP) to encourage primary schoolchildren to consume more fruit and vegetables, and a Travel to School Programme, (TSP) to promote sustainable modes of transport, car-pooling and public transport use in primary and secondary schools. The HEP is EU and government funded, the TSP entirely government funded. TSP adopts a flexible approach where schools can set their travel targets. School coordinators (teachers) cascade both programmes to classroom teachers. Methods: Seven of eight schools invited to participate based on predetermined criteria took part in the study. Face-to-face interviews (n=15) were conducted with teachers, project managers and key stakeholders using a topic guide developed by the international DEDIPAC team and informed by a prior systematic umbrella review of conditions influencing implementation. Data were coded in NVIVO using a common categorization matrix and thematic analysis carried out using parameters of the RE-AIM (Reach, Effectiveness, Adoption, Implementation, Maintenance) evaluation framework. Results: Good working relationships were critical to adoption, successful implementation and sustainability in line with findings from case studies in other EU countries. Organisational and leadership ability of coordinators was key to successful delivery. Incentives and rewards acted as motivators to engage children's interest, which motivated teacher and parent involvement. Particular challenges faced by the TSP included a lack of funding security and timetable constraints within secondary schools. HEP was based on well-funded external research with clearly defined core components and has been frequently externally evaluated. TSP core components were broad rather than specific, implementation was flexible and there was a lack of agreement among stakeholders on how targets were set and the accuracy of these. Conclusion: Good relationships, organisational and leadership ability, and secure funding were key conditions for implementation, sustainability and dissemination of promising public health interventions. The findings have informed the DEDIPAC-KH Pan European Toolbox set up for researchers and practitioners who want to develop, evaluate or implement multicomponent interventions on physical activity, sedentary behaviour or dietary behaviour.